Management of the Implementation of Arabic Language Programs in Increasing Learning Motivation - Qonita, Arieza; Mardiah, Ainul; Arifa, Zakiyah (JURNAL IJ-ATL, 2022)
This study aims to describe leadership, motivation, and communication in the institution of the Islamic Boarding School, whose members have achieved various achievements at the national and international levels. This study departs from the importance of good program implementation management to produce students who are competent in Arabic and able to compete at various levels. Factors such as participatory and democratic leadership, need-based motivation, and descending and transcendent communication, both formally and informally, verbally and in writing, determine the success of the program. This study uses a qualitative descriptive approach to explore the internal dynamics of the institution. The results show that the combination of inclusive leadership, relevant motivation, and effective communication contribute significantly to the achievement of the institution's achievements. This study provides a practical contribution in understanding the management of Islamic boarding school-based institutions and its relevance to the development of globally competitive Arabic language competencies.